Normative prompts reduce consumer food waste in restaurants. (July 2018) - Stöckli, Sabrina; Dorn, Michael; Liechti, Stefan
Highlights: Research needs to test anti-consumer-food-waste interventions. Prompts encourage diners to take away leftovers. Restaurants can apply prompts and social norms to save resources. Testing behavioral change interventions to foster sustainable food consumption is suggested. Abstract: This field study demonstrates that prompts reduce food waste in a restaurant. Based on the behavioral change literature, it was hypothesized that (1) informational prompts encourage consumers to reduce food waste, and that (2) an informational prompt with a normative message is more effective than a prompt with only an informative message. The results were mixed. As expected, diners who were exposed to prompts asked to take away their leftovers more frequently than diners who were exposed to no prompts. However, prompts with an informative and normative message were no more powerful than prompts with only an informative message.